O ensino de química em um curso técnico integrado: potencialidades para a docência - Bilar, Jéssica de Góes (2022)
The teaching of chemistry enables a broad contextualization with the students' reality, and in integrated technical high school, this possibility is greater, since it can be articulated with themes related to the technological axes of the courses. However, many times, in the classroom, chemistry is seen by students as one of the most complex subjects to understand, because they receive the concepts ready, in order to just exercise repetition, without reflection and contextualization. In this sense, it becomes necessary to evaluate how this curriculum component is being addressed in integrated technical high school, whether there is integration of the content worked in the subjects with vocational training. Therefore, the objective of this work is to investigate how the process of teaching chemistry occurs throughout the Integrated Technical Course in Agricultural and Livestock Husbandry at the Instituto Federal Farroupilha Campus São Vicente do Sul, and in light of this, propose the development of a didactic activity notebook for use by the teacher in the classroom, introducing the problematization of themes and the integration of the basic area with the technical area. The methodology used for this research was a case study with a quali-quantitative approach. Thus, the research is being developed in three stages: 1) a scientometric analysis of academic productions about the theme of this study; 2) a semi-structured interview with the chemistry teachers; and 3) the elaboration of a didactic activity notebook. The results of the first stage of this study indicate that 41.93% of the dissertations and theses do not use themes as a form of contextualization and problematization in the teaching of chemistry. As for the results of the second stage, they show that the chemistry teachers of this institution do not include contextualization and curriculum integration as a priority in their lesson plans. Thus, these results reinforce the importance of developing the last stage, which is the development of the didactic activity booklet, which is expected to effectively assist in the exercise of teaching and learning of students, as well as establish scientific and technological relations in the practice of chemistry.